2007
DOI: 10.1111/j.1463-1318.2007.01264.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical load and long‐term outcome for patients with Kock continent ileostomy

Abstract: The reoperation rate of patients with CI is high but the removal rate of the pouch is low and is not associated with a high rate of revision. CI is a good alternative to conventional ileostomy in patients not suitable for restorative proctocolectomy or where this procedure has failed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
35
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 19 publications
7
35
0
Order By: Relevance
“…242 initial pouch retention rates have been reported in up to 96% after 1 year, 235, 237 with a 71% cumulative success rate at 29 years in 1 study. 243 for the two-thirds of patients with a functional continent ileostomy, the reported quality of life is similar to that described for patients with iPaa. 243 for the two-thirds of patients with a functional continent ileostomy, the reported quality of life is similar to that described for patients with iPaa.…”
Section: Continent Ileostomy Is An Alternative For Patients With Uc Wsupporting
confidence: 71%
“…242 initial pouch retention rates have been reported in up to 96% after 1 year, 235, 237 with a 71% cumulative success rate at 29 years in 1 study. 243 for the two-thirds of patients with a functional continent ileostomy, the reported quality of life is similar to that described for patients with iPaa. 243 for the two-thirds of patients with a functional continent ileostomy, the reported quality of life is similar to that described for patients with iPaa.…”
Section: Continent Ileostomy Is An Alternative For Patients With Uc Wsupporting
confidence: 71%
“…Although bone and soft tissues seems to adhere firmly to a titanium implant, the described properties of the endothelial lining of the bowel wall may make such fusion more difficult. Thus, experience from clinical procedures such as the everted enterostoma or the intussusception of an ileocecal valve have demonstrated that adhesions may well stabilize the construction temporarily but this junction will fail with the passage of time 33–35. Special measures were therefore taken to overcome this problem.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of complications after CI is in the same order of magnitude as after IPAA. Within 20 years, about half the patients with CI will need one or several salvage procedures mainly because of nipple-valve slippage [18][19][20]. The incidence of complications with a conventional ileostomy is, however, not negligible and Table 2 Clinical characteristics, complications and outcome in patients with continent ileostomy (CI) after the procedure of the failed ileal pouch-anal anastomosis (IPAA even with modern ileostomy appliances many patients endure many kinds of discomfort [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%